Pre- and post-pandemic risk perceptions and worries - Wolff, Katharina; Larsen, Svein (Frontiers in Psychology, 2024)
Intro: The present study is a cross-sec0onal inves0ga0on of worries and risk percep0ons regarding various hazards and des0na0ons comparing measures obtained before, during and a?er the Covid-19 pandemic. Methods: Ques0onnaire data were collected among tourists to Norway during the summer seasons of 2012 (N = 2669), 2019 (N = 1666) and 2022 (N = 956), as well as in a representa0ve sample of Norwegians in 2020 (N = 1003). Results: Results show a general decline in worries and risk percep0ons a?er compared to before the pandemic. There is only one excep0on from this paDern, the perceived risk for infec0ous diseases is slightly increased in 2022 compared to earlier. Conclusions: Results highlight the importance of employing cross-sec0onal or longitudinal data to inves0gate changes in risk percep0ons over 0me. The findings also indicate that pessimis0c predic0ons about a con0nued decline in tourist travel seem unwarranted.